Incentives for accelerating the production of Covid-19 vaccines in the presence of adjustment costs - Claudius Gros; Daniel Gros (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Delays in the availability of vaccines are costly as the pandemic continues. However, in the presence of adjustment costs firms have an incentive to increase production capacity only gradually. The existing contracts specify only a fixed quantity to be supplied over a certain period and thus provide no incentive for an accelerated buildup in capacity. A high price does not change this. The optimal contract would specify a decreasing price schedule over time which can replicate the social optimum.
Keywords: 330; Coronavirus; Impfung; Produktionskapazität; Leistungsanreiz; USA